The Effect of Entrepreneurial Dimension on Corporate Reputation Among Corporations in the Municipality of Santo Tomas, Davao Del Norte - Balgoma, Jannah Mikaela V.; Espinosa, Brindel D.; Almagro, Ronald E. (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study focused on the connection between entrepreneurial dimensions and corporate reputation among corporations. Using the Sloven equation, the intended sample size was 148 out of the 240 workers who participated in the research as responders. The method used to choose the respondents was universal sampling. The data obtained using two adjusted questionnaires were analyzed using the mean and Pearson r. The results showed that workers usually exhibit the entrepreneurial dimension in terms of competitive aggression. However, a company’s reputation for emotional appeal is always present. The findings showed that among employees of a firm, there was a substantial correlation between the entrepreneurial component and corporate reputation. The findings proposed that corporations should create programs supporting employees’ bold activities with clear risk evaluations and training. Besides, representatives must remain informed about industry trends, competitor activity, and the company’s objectives. Moreover, employees must build on trust, shared purpose, and respect, which can create more meaningful and sustainable connections among employees. In addition, corporations must emphasize surveys to recognize the value of exceptional personnel, attract them, provide them with benefits, and offer them competitive compensation. Future researchers will explore the impacts of entrepreneurial dimensions (e.g., innovativeness, risk-taking, pro-activeness, and competitive aggressiveness) on corporate reputation among corporations. Understanding which dimensions have the most prominent impact can assist employees in working efficiently.